Investment under uncertainty and regulation of new access networks - Roman Inderst; Martin Peitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Contractual and regulatory provisions for access affect incentives to invest in an upgraded network and, in particular, a next-generation access network. Investment decisions are made under uncertainty and have to be made over time. This papers provides a framework for taking uncertainty, risk aversion, and the timing of investment explicitly into account. First, it evaluates various access price policies in a framework in which the incremental value over the legacy network is uncertain. Second, introducing risk aversion, the access price structure turns out to be critical for the risk profile of the investing telecom operator and of the access-seeking alternative operator. Third, some implications of the time structure of access payments are derived.
urn:nbn:de:bsz:180-madoc-332965
Keywords: L1; L5; 330; NGA; investment under uncertainty; access price rule; telecommunications